2013
DOI: 10.1111/ijfs.12391
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of proximate composition and amino acid in farmed and wild Pseudobagrus ussuriensis muscles

Abstract: Summary The proximate composition and amino acid compositions of the muscle of wild and farmed Pseudobagrus ussuriensis were compared. The lipid content of the farmed fish was significantly higher, while moisture content was significantly lower, than those of the wild fish. Pseudobagrus ussuriensis protein has a well‐balanced amino acid composition. The percentages of total amino acids, essential amino acids, nonessential amino acids and delicious amino acids were significantly higher in the wild than those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 28 publications
8
30
3
Order By: Relevance
“…A general trend in numerous studies was observed, where farmed fish tended to have higher fat content and lower moisture content compared to wild individuals of the same species (Fuentes et al, 2010;González et al, 2006;Olsson et al, 2003;Rodríguez-Barreto et al, 2012;Wang et al, 2014;Zhao et al, 2010). However, no such trend was apparent in the current study, in fact the wild yellowtail had marginally (not significant) higher fat and lower moisture contents compared to those sampled from the wild.…”
Section: Proximate Compositioncontrasting
confidence: 63%
“…A general trend in numerous studies was observed, where farmed fish tended to have higher fat content and lower moisture content compared to wild individuals of the same species (Fuentes et al, 2010;González et al, 2006;Olsson et al, 2003;Rodríguez-Barreto et al, 2012;Wang et al, 2014;Zhao et al, 2010). However, no such trend was apparent in the current study, in fact the wild yellowtail had marginally (not significant) higher fat and lower moisture contents compared to those sampled from the wild.…”
Section: Proximate Compositioncontrasting
confidence: 63%
“…The essential amino acid indexes (EAAI) were calculated according to Oser () as the geometric mean of the essential amino acid ratios and the food protein relative to per cent levels in whole egg protein using following equation, which was also recently reported by Wang et al (), Olu and Adediran () and Jiang et al ():Essential Amino Acid Index,0.333333emEAAI=[false(100×EAA1false/EAA1EGfalse)×false(100×EAA2false/EAA2EGfalse)××false(100×EAAnfalse/EAAnEGfalse)]nwhere, “ n ” is the number of amino acids (considering pairs such as methionine + cystine)…”
Section: Methodsmentioning
confidence: 98%
“…The amino acid score (AAS), chemical score (CS) and essential amino acid index (EAAI) were calculated using the following formula (Wang et al, ):AAS =0.333333em0.625×aaAA(FAO/WHO)CS =0.333333em0.625×aaAA(egg)EAAI =0.333333em100AAE×100BBE×100CCE××100GGEn…”
Section: Methodsmentioning
confidence: 99%